2018
DOI: 10.1016/j.jinf.2018.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Neisseria gonorrhoeae molecular typing for understanding sexual networks and antimicrobial resistance transmission: A systematic review

Abstract: HighlightsCombined molecular and epidemiological data can describe the spread of gonorrhoea.Sexual networks can be inferred from molecular clusters of infection.Gender and sexual orientation are commonly used to characterise these networks.Application of these data within gonorrhoea control interventions is limited.Future studies should focus on evaluating molecular typing data in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
(269 reference statements)
0
11
0
Order By: Relevance
“…MSMW with gonorrhoea were scattered within MSM and heterosexual networks suggesting a possible role in bridging transmission between MSMO and females, although given our sampling frame, it is not possible to say whether these were responsible for the commencement of transmission clusters. Previous studies (predominantly using NG-MAST) have varied in the extent of bridging identified across heterosexual and MSM-associated networks 23 . For example, Choudhury et al found that MSM comprised only 1.7% of cases associated with the 14 major heterosexual NG-MAST groups in a large study from London in 2004 24 .…”
Section: Discussionmentioning
confidence: 99%
“…MSMW with gonorrhoea were scattered within MSM and heterosexual networks suggesting a possible role in bridging transmission between MSMO and females, although given our sampling frame, it is not possible to say whether these were responsible for the commencement of transmission clusters. Previous studies (predominantly using NG-MAST) have varied in the extent of bridging identified across heterosexual and MSM-associated networks 23 . For example, Choudhury et al found that MSM comprised only 1.7% of cases associated with the 14 major heterosexual NG-MAST groups in a large study from London in 2004 24 .…”
Section: Discussionmentioning
confidence: 99%
“…WGS also can contribute evidence toward the development of rapid antimicrobial susceptibility tests to improve treatment decisions (8,9). However, few N. gonorrhoeae WGS studies have been conducted in England, and none include representative geographic coverage over time (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21] However, few studies have included sufficient clinical and sexual behaviour data to explore sexual mixing patterns between different sociodemographic groups and how mixing might influence STI and HIV transmission risk. 22 To inform public health infection control efforts, we wholegenome sequenced more than 1200 N gonorrhoeae isolates with linked clinical and sociodemographic data collected in five sexual health clinics in England over a 4year period. We investigated sexual mixing in N gonorrhoeae transmission networks between MSM, men reporting heterosexual behaviours, and women, and between MSM with and without HIV.…”
Section: Introductionmentioning
confidence: 99%